2005
DOI: 10.1002/adem.200500044
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage Fracture of Brittle Semiconductors from the Nanometre to the Centimetre Scale

Abstract: The objective of this paper is to present the fundamental phenomena occurring during the scribing and subsequent fracturing process usually performed when preparing surfaces of brittle semiconductors. In the first part, an overview of nano‐scratching experiments of different semiconductor surfaces (InP, Si and GaAs) is given. It is shown how phase transformation can occur in Si under a diamond tip, how single dislocations can be induced in InP wafers and how higher scratching load of GaAs wafer leads to the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…1 This method has many other potential applications in diverse fields, e.g., investigation of phase transformations, 2,3 thin film delamination, 4 and/or cleavage of materials. 5,6 Thus, indentation mechanics is extensively described in several text books. 7,8 Most scientists agree that, in III-V semiconductors, the nucleation of dislocations, also called the elastic-plastic transition, is associated with the pop-in in the load-displacement curve in nanoindentation.…”
Section: Introductionmentioning
confidence: 99%
“…1 This method has many other potential applications in diverse fields, e.g., investigation of phase transformations, 2,3 thin film delamination, 4 and/or cleavage of materials. 5,6 Thus, indentation mechanics is extensively described in several text books. 7,8 Most scientists agree that, in III-V semiconductors, the nucleation of dislocations, also called the elastic-plastic transition, is associated with the pop-in in the load-displacement curve in nanoindentation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, its material properties will dependence on crystal orientation and the principal characteristics are given in Table 1. The preferential cleavage plane is known to be {110} which is consistent with the lowest K IC value in Table 1 [1,[7][8][9][10][11]. The average fracture strength of GaAs wafers measured from micromechanical cantilever beam structure tests is more or less 2.4 GPa [17].…”
Section: Methodssupporting
confidence: 57%
“…It has already been observed that, by and large, 5 different phenomena occur when scratching semi-conductors [1] and glasses [4]. Figure 2, taken from [1], illustrated these 5 regimes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations